The devil's paintbox - McKernan, Victoria (New York : Alfred A. Knopf, 2009)
In 1865, fifteen-year-old Aiden and his thirteen-year-old sister Maddy, penniless orphans, leave drought-stricken Kansas on a wagon train hoping for a better life in Seattle, but find there are still many hardships to be faced.
English language and literature.
Keywords: Frontier and pioneer life -- West (U.S.) -- Fiction; Overland journeys to the Pacific -- Fiction; Siblings -- Fiction; Orphans -- Fiction; West (U.S.) -- History -- 1860-1890 -- Fiction; Seattle (Wash.) -- History -- 19th century -- Fiction